Drupal 7 bible - Shreves, Ric.; Dunwoodie, Brice (Indianapolis, IN : Wiley, 2011)
Web content management systems (CMS) are hot, and the flexible and powerful open source Drupal is one of the most popular. Whether you're designing a new Web site or looking for an easier way to publish content to your existing site, this practical book shows you how to use Drupal 7 to do it. Learn how to create, manage, and present content via public or private Web sites, even if you don't have deep technical skills. --Book Jacket.
Note continued: ch. 34 Making an Accessible Site -- What Is Accessibility? -- Drupal and Accessibility -- Improving theme accessibility -- Support semantic structure -- Avoid tables -- Don't rely on JavaScript -- Use system fonts for your nav menus -- Use appropriate capitalization -- Use a suitable color scheme -- Order elements on the screen logically -- Make sure your text resizes -- Use jump links -- Make forms accessible -- Provide hover states and visited states -- Provide alternatives to applets and plugins -- Avoid requiring timed responses -- Creating accessible content -- Use headings and styles correctly -- Use lists correctly -- Use alt image attributes -- Summarize graphs and charts -- Summarize multimedia -- Format tabular data properly -- Summary -- ch. 35 Handling Change Management -- Taking a Site Offline -- Backing Up Your Site -- Restoring from a Backup -- Using the Update Manager Module -- Managing Site Upgrades -- Handling minor upgrades -- Handling major version upgrades -- Summary -- pt. VIII Appendixes -- Appendix A The Directory Structure of a Drupal Installation -- Appendix B Location of Key Files -- Aggregator -- Module -- Style Sheets -- Templates -- Blocks -- Module -- Style Sheets -- Templates -- Blog Content Type -- Module -- Book Content Type -- Module -- Style Sheets -- Templates -- Comments -- Module -- Style Sheets -- Templates -- Contact Module -- Module -- Forum -- Module -- Style Sheets -- Templates -- Menus -- Module -- Style Sheets -- Nodes -- Module -- Style Sheets -- Templates -- Polls -- Module -- Style Sheets -- Templates -- Profile -- Module -- Style Sheets -- Templates -- Search -- Module -- Style Sheets -- Templates -- System -- Module -- Style Sheets -- Templates -- Taxonomy -- Module -- Style Sheets -- Templates -- Users -- Module -- Style Sheets -- Templates -- Appendix C Installing XAMPP -- Appendix D Installing MAMP -- Appendix E Beyond the Book -- Additional Help Resources Online -- The Help Files Inside Drupal -- Online Help and Support Resources -- Using Community Support Options -- Finding Commercial Support.
Includes bibliographical references and index.
Print version record.
John Wiley and Sons
Keywords: Drupal (Computer file); Drupal (Computer file); Drupal (Computer file); Web site development; Web sites -- Design; Open source software; Sites Web; Sites Web -- Conception; Logiciels libres; COMPUTERS -- Web -- Web Programming; Open source software; Web site development; Web sites -- Design